Human resource practices in a non governmental organization: A case study at Malaysian Nature Society (MNS) - Nor Aini, Zainol Rashid (2015)
Malaysian Nature Society (MNS) is one of the largest and longest surviving NGOs in Malaysia. MNS is dependent upon membership fees through subscriptions as a main source of income; however it is not adequate to cover the cost of running MNS. The biggest challenge in MNS is to seek financial support through projects to maintain and sustain the organization. This exploratory qualitative research was carried out to study the human resource management practices in an Non-Governmental Organization (NGO) in a Malaysian context. Issues and challenges were also examined. Applying saturation and purposive sampling in this study, ten respondents were interviewed. Data gathered were transcribed, sorted, coded and analysed manually using Excel. Findings in this study revealed three themes, namely leadership, career development, and compensation and benefits. This study proposed with effective leadership, career development, and compensation and benefits, employees will perform better, increase retention and reduce high staff turnover. Majority of the participants also mentioned about the low salaries. Salary is the biggest motivator and MNS should look into a salary revision periodically